Factors predictive of clinical outcome in advanced hepatocellular carcinoma patients receiving ramucirumab treatment: A real‐world experience - Po‐Ting Lin; Min‐Hua Hung; Shih‐Chieh Shao; Hui‐Yu Chen; Yuk‐Ying Chan; Kai‐Cheng Chang; Shi‐Ming Lin; Huang‐Tz Ou (Cancer Medicine, 2023)
Abstract Purpose The aim of this study was to investigate the factors predictive of clinical outcome in advanced hepatocellular carcinoma patients receiving ramucirumab treatment. Methods We conducted a retrospective study using a multi‐institutional electronic medical records database in Taiwan. We included advanced HCC patients newly receiving ramucirumab as second‐line or beyond systemic therapy between January 2016 and February 2022. The clinical outcomes were median progression‐free survival (PFS) based on the modified Response Evaluation Criteria in Solid Tumors (mRECIST), overall survival (OS) and adverse events. We applied Kaplan–Meier methods to estimate median PFS and OS. Uni‐variable and multi‐variable Cox regression models were applied to identify the prognostic factors. Results We included 39 ramucirumab naive users with a median age of 65.5 (IQR: 57.0–71.0) years and treatment time of 5.0 (3.0–7.0) cycles, of whom 82.1% were male and 84.6% were Barcelona Clinic Liver Cancer (BCLC) stage C. After median follow‐up time of 6.0 months, 33.3% of patients' AFP level had decreased more than 20% within 12 weeks. The median PFS and OS were 4.1 months and non‐reach, respectively. Moreover, tumor burden beyond the up‐to‐11 criteria (HR: 2.95, 95% CI: 1.04–8.38) and a decrease in estimated glomerular filtration rate of more than 10% within 12 weeks (HR: 0.31, 0.11–0.88) were significantly related to PFS in the multi‐variable analysis. No patient discontinued ramucirumab during the treatment on account of side effects. Conclusion Ramucirumab was an effective treatment option with good AFP response for advanced HCC patients in real‐world experience. Tumor burden beyond the up‐to‐11 criteria and a decrease in estimated glomerular filtration rate were independent predictive factors for progression‐free survival.